PENGARUH PENDEKATAN PEMBELAJARAN TAKTIS TERHADAP KETERAMPILAN SEPAKBOLA SISWA KELAS XI SMA LABSCHOOL UPI KOTA BANDUNG - Ricky Fernando (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research examines the effectiveness of a tactical learning approach on the learning outcomes of football skills. The results of this study are expected to serve as an alternative solution to improving the quality of football learning. The method used in this research is experimental, employing a pre-test and post-test design. The population in this study consisted of 60 students from class XI at High School Labschool UPI Bandung. The sample was selected using purposive sampling techniques. The research was conducted over two months, with a total of 18 treatment meetings, held three times on Sundays. The instruments used in this study included skill tests and football ability tests (GPAI). For high school students, the football skill test (pre-test and post-test) consisted of four components: passing and stopping, heading, dribbling, and shooting, along with the GPAI to assess overall playing ability. Based on the results of the analysis, it can be concluded that the tactical learning approach has a significant effect on improving football skill learning outcomes.